Learning Disabilities in Extremely Low Birth Weight Children and Neurodevelopmental Profiles at Preschool Age - Squarza, Chiara; Picciolini, Odoardo; Gardon, Laura; Giannì, Maria L.; Murru, Alessandra; Gangi, Silvana; Cortinovis, Ivan; Milani, Silvano; Mosca, Fabio (Frontiers in Psychology, 2016)
At school age extremely low birth weight (ELBW) and extremely low gestational age (ELGAN) children are more likely to show Learning Disabilities (LDs) and difficulties in emotional regulation. The aim of this study was to investigate the incidence of LDs at school age and to detect neurodevelopmental indicators of risk for LDs at preschool ages in a cohort of ELBW/ELGAN children with broadly average intelligence. All consecutively newborns 2001-2006 admitted to the same Institution entered the study. Inclusion criteria were BW < 1000 g and/or GA < 28 weeks. Exclusion criteria were severe cerebral injuries, neurosensory disabilities, genetic abnormalities and/or a Developmental Quotient below normal limits (<1 SD) at 6 years. The presence of learning disabilities at school age was investigated through a parent-report questionnaire at children’s age range 9-10 years. Neurodevelopmental profiles were assessed through the Griffiths Mental Development Scales at 1 and 2 years of corrected age and at 3, 4, 5 and 6 years of chronological age and were analysed comparing two groups of children: those with LDs and those without. At school age 24 on 102 (23.5%) of our ELBW/ELGAN children met criteria for LDs in one or more areas, with 70.8% comorbidity with emotional/attention difficulties. Children with LDs scored significantly lower in the Griffiths Locomotor and Language subscales at 2 years of corrected age and in the Personal-social, Performance and Practical Reasoning subscales at 5 years of chronological age. Our findings suggest that, among the early developmental indicators of adverse school outcome, there is a poor motor experimentation, language delay and personal-social immaturity. Cognitive rigidity and poor ability to manage practical situations also affect academic attainment. Timely detection of these early indicators of risk is crucial to assist the transition to school.